FUNCTIONAL AND MOTOR ABILITIES OF CHILDREN DIAGNOSED WITH CEREBRAL PALSY - Gross, N.A.; Sharova, T.L.; Molokanov, A.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to integrate the baseline characteristics of the functional and motor abilities of disabled children and their deviations from the norm for use in planning physical loads during a rehabilitation process. Methods and structure of the study. To systematize the characteristics determining the functional and motor fitness of disabled children and assess the degree of its compliance with the indices in healthy children, we consolidated the data obtained in the studies of 2017-2020. The studies were carried out before the start of the rehabilitation course and involved 3-16 year-old disabled children, both males and females, (n=95) of all five levels of development of the gross motor functions on the GMFCS scale. The following methods were applied: anthropometry, pulsometry, heart rate variability, stabilometry, podometry, pedagogical testing of motor abilities. The subjects’ movements were assessed over 54 parameters from the following initial positions: lying on the back and stomach, sitting on the floor and chair, standing and in motion (crawling and walking). Results and conclusion. Children diagnosed with cerebral palsy, who lead a sedentary lifestyle, lag behind healthy children in terms of all the studied parameters, which necessitates increasing the effectiveness of the rehabilitation process by increasing the overall motor activity. The heart rate variability rates in the initial state indicated that the body of children with cerebral palsy is characterized by the state of detraining and impaired functional abilities.